Adaptive event‐triggered output feedback control for a class of p‐normal nonlinear systems with sensor failure. (7th August 2020) - Li, Min; Li, Shi; Shu, Feng; Xiang, Zhengrong
Summary: This article investigates the problem of global adaptive output feedback control for a class of p ‐normal nonlinear systems with time‐varying sensor failure and unknown growth rate via an event‐triggered strategy. Due to the existence of time‐varying sensor failure, only the system output with sensor failure is available for feedback control design. To overcome this obstacle, an adaptive reduced‐dimensional observer using only failure output is constructed. Subsequently, a novel adaptive event‐triggered controller is designed by virtual of a dynamic gain technique, under which all the states of the considered closed‐loop systems are bounded as well as the proposed event‐triggered mechanism is Zeno‐free. Finally, two examples are provided to demonstrate the validity of the presented control method.